Endothelial Colony‐Forming Cells in Young Adults Born Preterm: A Novel Link Between Neonatal Complications and Adult Risks for Cardiovascular Disease. Issue 14 (17th July 2018) - Bertagnolli, Mariane; Xie, Li Feng; Paquette, Katryn; He, Ying; Cloutier, Anik; Fernandes, Rafael Oliveira; Béland, Chanel; Sutherland, Megan R.; Delfrate, Jacques; Curnier, Daniel; Bigras, Jean‐Luc; Rivard, Alain; et al.
Abstract : Background: Preterm birth is linked to cardiovascular risks and diseases. Endothelial progenitor cells play a critical role in vascular development and repair. Cord blood endothelial progenitor cells of preterm‐born infants, especially endothelial colony‐forming cells (ECFC), show enhanced susceptibility to prematurity‐related pro‐oxidant stress. Whether ECFC dysfunction is present in adulthood following preterm birth is unknown. Methods and Results: This cross‐sectional observational study includes 55 preterm‐born (≤29 gestational weeks) young adults (18–29 years old, 38% male) and 55 sex‐ and age‐matched full‐term controls. ECFC were isolated from peripheral blood; cell proliferative and vascular cord formation capacities were assessed in vitro. Daytime systolic blood pressure was higher, whereas glucose tolerance and body mass index were lower in preterm‐born subjects. ECFC colonies grew in culture for 62% of full‐term‐ and 58% of preterm‐born participants. Preterm‐born participants have formed ECFC colonies later in culture and have reduced proliferation compared with controls. Only in preterm‐born individuals, we observed that the later the ECFC colony grows in culture, the worse was overall ECFC function. In addition, in preterms, elevated systolic blood pressure significantly correlated with reduced ECFC proliferation (rS =−0.463; P =0.030) and numbers of branches formed on matrigel (rS =−0.443; P =0.039). In preterm‐born subjects, bronchopulmonary dysplasia was associated with impaired ECFC function, whereas exposure to antenatal steroids related to better ECFC function. Conclusions: This study is the first to examine ECFC in preterm‐born adults and to demonstrate ECFC dysfunction compared with full‐term controls. In the preterm‐born group, ECFC dysfunction was associated with bronchopulmonary dysplasia, the major prematurity‐related neonatal morbidity, and with increased systolic blood pressure into adulthood.